To seal or to reveal effects of self monitoring and self-esteem on identity management in facebook. - Maguad, Rosanna Danica B.
This quantitative study sought to explore the Facebook identity management of respondents who vary on self-esteem and self-monitoring variables and the amount of information they maintain on their profiles. The participants of this study were 175 college students of University of Antique. There is no difference in the identity management of people with high and low self-esteem. Both use projection strategy more than suppression strategy. This shows that both groups find Facebook as an effective avenue in raising their self-esteem. Furthermore, there is no significant difference on projection strategy scores between self-esteem groups. On the other had, there is a difference in the identity management of self-monitoring groups. High self-monitors use projection strategy more than the suppression strategy while low self-monitors use both projection and suppression strategies. They are also suppress more than high self-monitors. The said strategies were used because high self-monitors need to fulfill interaction-oriented goals while low self-monitors find Facebook as an aversive environment for self-presentation. Further, there is no significant difference in the amount of Facebook information for both self-esteem and self-monitoring groups. Thus, this means that a person who uses projection strategy does not necessary maintain a highly detailed profile. Factors such as number of friends, the user?s need for popularity, and interaction goals are factors affecting richness of Facebook information in one?s profile.